Leakage of photocurrent： an alternative view on I-V curves of solar cells - 周桃飞 熊康林 张敏 刘磊 田飞飞 张志强 顾泓 黄俊 王建峰 董建荣 徐科 (Journal of semiconductors, 2015)
An altemative way is proposed to interpret I-V characteristics of GalnP single-junction solar cells by position-dependent leakage ofphotocurrent. With this approach, the I-V curves of solar cells under non-uniform illumination are well analyzed. The effective spreading resistance is also extracted to understand the dynamic behavior of between the open-circuit voltage and short-circuit current points. The conditions under which the one- diode model will fail are addressed in detail. These analyses are also applicable for a characterization of the I-V curves with lateral voltage distribution under uniform illumination.